A Homoeopathic Lens on Anatomy; Using Kents Repertory for Deeper Understanding (Homoeopathy for All, 2025)
Background: anatomy forms the  foundational structure of medical  science, providing a detailed  understanding of the human  body’s organs, systems, and their  interconnections. In homeopathy,  though the focus remains on  individualized symptoms and  holistic healing, a sound anatomical  understanding is crucial for accurate  remedy selection and effective case  management. Dr. James Tyler Kent’s  Repertory of the homeopathic  Materia Medicais one of the most  influential tools, it subtly integrates  anatomical references that guide  practitioners towards a deeper  comprehension of the patient’s  condition, not just at the functional  but also at the structural level.  Exploring through the lens of Kent’s  repertory allows homeopaths to  refine their approach to case analysis,  especially in localizing symptoms,  understanding pathological  tendencies, and correlating them  with constitutional indications. This  integration enhances the precision  of remedy selection, particularly  when symptoms are expressed  in specific anatomical regions.  This article seeks to bridge the  conventional anatomical perspective  with the unique symptom - based  classification of Kent’s repertory,  promoting a more integrated and  clinically insightful approach to  homeopathic practice.  Objective- Briefly combining about  anatomy subject with Kent repertory  - to know the first year CBDC Batch  students how the Kent repertory will  help to study the anatomy what are  the location and organs or parts how  we can see in the Kent repertory  which are the rubrics and sub rubrics  to look for. Methods- How to use the Kent  repertory and it has been constructed  in macro and micro construction  chapters and rubrics and sub rubrics  has been arranged and remedies and  cross references arranged, how these  chapters we can apply to anatomy.  This could involve an exploration  of specific symptoms or anatomical  concepts found in the repertory and  how they correlate with anatomical  structures or conditions. Results- Highlighting the chapter  which has the location related  rubrics and sub rubrics and the  specific remedy for the particular  remedy. Implication- Now at least students  will able to find out the exact  location or parts or organs related  rubrics how to search and where  to search in Kent repertory in our  day to day clinical practice. This  approach deepens the understanding  of anatomy or contribute to a more  holistic or integrative approach to  healthcare. Conclusion: NCH has applied  Kent repertory for first year CBDC  batch for three subjects anatomy,  physiology and psychology  correlation with Kent repertory  related chapters and rubrics and sub  rubrics how can students will able  find or search in Kent repertory.  Further exploration of anatomical  correlations across other repertories  and integration with modern  diagnostic methods can strengthen  this bridge between traditional  and contemporary practice.  Ultimately, this method enriches  the art and science of homoeopathy,  empowering practitioners with  clarity, confidence, and clinical  precision.
Keywords: Eclectic; STME; Dr. Phelan,; Lucy; CBDC; NCH; LSMC